2014
DOI: 10.1007/s11829-014-9327-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical signatures affecting host choice in the Eucalyptus herbivore, Gonipterus sp. (Curculionidae: Coleoptera)

Abstract: Abstract-It is well-known that herbivorous insects respond to host plant volatiles. Yet details of how these insects perceive the complex profile of volatiles from different potential host plants has not been studied for most insects. Gonipterus spp. are important pests of Eucalyptus worldwide, but differ in their preference for different species of this host. In this study we consider whether host volatiles affect the host choice for a Gonipterus sp., and we characterize the response of the female insect to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Eucalyptol and the E. globulus leaves volatile were electrophysiologically active in Gonipterus spp. females with a mean response of 0.76 mV (Bouwer et al 2014). The anethole results showed that the antennae of both sexes of A. superciliosus can perceive this compound with a response higher in females than males.…”
Section: Discussionmentioning
confidence: 88%
“…Eucalyptol and the E. globulus leaves volatile were electrophysiologically active in Gonipterus spp. females with a mean response of 0.76 mV (Bouwer et al 2014). The anethole results showed that the antennae of both sexes of A. superciliosus can perceive this compound with a response higher in females than males.…”
Section: Discussionmentioning
confidence: 88%
“…According to the literature, some secondary metabolites have been identified in E. globulus. These are characterized by the presence of mixtures of terpenes and terpenoids of C10 and C15 (Tyagi and Malik, 2011), which would be the main components of the essential oil, and are found in a variety of plant families in different ratios for each species (Külheim et al, 2011;Bouwer et al, 2014), the eucalyptus species produce a great variety of these volatile compounds in significant amounts, which accumulate in glands distributed in the parenchymal tissue and in the bark of the tree (Özgenc et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Several secondary metabolites produced and emitted by E. globulus specimens exert effects on insect physiology and behavior, playing an important role in the plant-insect interaction (Bouwer et al, 2014). In order to understand the role of volatile organic compounds emitted by E. globulus when the insect is attracted to this non host-plant, dichloromethane extracts of E. globulus were analyzed through gas chromatography-mass spectrometry to identify main compounds and extract's composition.…”
Section: Introductionmentioning
confidence: 99%
“…He et al. 2000; Paiva & Mateus, 2012), and iv) γ ‐terpinene, a compound reported by Bouwer, Slippers, Wingfield and Rohwer (2014) as being the main responsible for the dissimilar susceptibility of Gonipterus sp. 2 to different host species.…”
Section: Discussionmentioning
confidence: 99%